2014
DOI: 10.15527/ejre.201426254
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviors related agrochemical use among rubber farmers in Southern of Thailand

Abstract: The study objective was to evaluate the knowledge, beliefs and behaviors regarding agrochemical safety behaviors among farmers among farmers in the Khogyang community, Trang province, Thailand between the period September and December 2012. The principles of Health Belief Model and community participatory approach were applied to develop a comprehensive strategy to reduce agrochemical risk their behavior. 316 farmers from 8 villages in Khogyang community were recruited. The mean scores of the 3 variables (know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There have been reports of strong associations between exposure to pesticides and cancer 10 , and studies have shown that the exposure of pregnant women and breastfeeding mothers to pesticides is a risk factor for low birth weight, congenital birth defects, growth defects, learning disabilities and miscarriage 1,11 . Previous evidence suggests that farmers have awareness and a basic understanding of insecticides, pesticides and various other chemicals used in farming practices [12][13][14] However, this awareness and knowledge alone might not lead to reduced use of the various chemicals when farming. Health literacy (HL) is a relatively new concept for social and medical sciences research.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of strong associations between exposure to pesticides and cancer 10 , and studies have shown that the exposure of pregnant women and breastfeeding mothers to pesticides is a risk factor for low birth weight, congenital birth defects, growth defects, learning disabilities and miscarriage 1,11 . Previous evidence suggests that farmers have awareness and a basic understanding of insecticides, pesticides and various other chemicals used in farming practices [12][13][14] However, this awareness and knowledge alone might not lead to reduced use of the various chemicals when farming. Health literacy (HL) is a relatively new concept for social and medical sciences research.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that education may increase workers' general knowledge and analytic power for better understanding of pesticides' detrimental effects, using personal protective equipment, and avoiding risks that endanger users of pesticides. Suklim and Khan reported a significant relationship between education and protective behaviors of farmers against pesticides (33,37). There was no significant relationship between income, protection motivation, and behavior in the current study, while in the study of Khan, income had a negative relationship with risk perception (37).…”
mentioning
confidence: 99%